The Effect of the Application of Chemical Fertilizer and Arbuscular MyCorrhizal Fungi on Maize Yield and Soil Microbiota in Saline Agricultural Soil - Ye Yuan; Zhengjun Feng; Shengxin Yan; Junjie Zhang; Huiping Song; Yan Zou; Dapeng Jin (Journal of Fungi)
The overuse of chemical fertilizers not only leads to resource wastage but also causes problems such as environmental pollution and soil degradation. In particular, crop growth in saline–sodic soils is severely restricted due to high salinity and alkalinity, further exacerbating challenges in agricultural production. The aim of this study was to investigate different fertilization strategies that combine chemical fertilizer reduction with arbuscular mycorrhizal fungi (AMF) for improving saline–sodic soils and to assess the effects of these protocols on crop yield, soil properties, and microbial communities. Field experiments across two sites (BeiWuLao and XuJiaZhen) demonstrated that integrating AMF with CF reduction (AHCF treatment) significantly enhanced maize yield by 23.5% at BeiWuLao (from 11,475 to 14,175 kg/ha) and 81.2% at XuJiaZhen (from 7245 to 13,125 kg/ha) compared to conventional fertilization (CK) (p < 0.01). Soil nutrient analysis revealed substantial improvements: available potassium (AK) increased by 77.7% (61.35 vs. 39.33 mg/kg), available phosphorus (AP) by 33.9% (20.50 vs. 15.50 mg/kg), ammonium nitrogen (AN) by 57.3% (64.17 vs. 40.83 mg/kg), and soil organic matter (SOM) by 96.4% (46.98 vs. 23.91 mg/kg) under AHCF treatment (p < 0.05). Although pH and electrical conductivity (ECe) remained unaffected, AMF inoculation shifted microbial composition, elevating salinity-tolerant taxa such as Actinobacteria (+24.7%) and Anabaena. Beta diversity analysis (PCoA) confirmed distinct microbial community structures between treatments, with ECe and AN identified as primary drivers of bacterial (RDA variance: 74.08%) and fungal (RDA variance: 54.63%) communities, respectively. Overall, the combination of chemical fertilizer reduction and AMF effectively improved soil fertility, microbial community structure, and crop yield. These findings have important implications for improving saline soils and promoting environmental sustainability.